Exchange rates and economic fundamentals : a framework for analysis - Clark, Peter...[et al] (IMF WashingtonUS, 1994)
Summarizes the methods and types of indicators that are often employed, both inside and outside the IMF, to assess whether exchange rates are broadly in line with economic fundamentals. Discusses the assessment of exchange rates based on measures of international competitiveness. Provides a framework for the analysis of the determinants of equilibrium real exchange rates.